Self-similarity in the wake of a semi-submersible offshore wind turbine considering the interaction with the wake of supporting platform. (August 2020) - Xiong, Xue-Lu; Lyu, Pin; Chen, Wen-Li; Li, Hui
Abstract: An experimental study of the wake characteristics of a semi-submersible offshore wind turbine model was performed in a wind tunnel and wave flume. The velocity distribution in the vertical direction was obtained with a four-hole pressure probe. First, a self-similarity analysis of the streamwise velocity deficit disclosed the inability of the Gaussian-like wake models for predicting the velocity deficit in regions influenced by the platform. The shelter model can be adopted for the consideration of the platform wake. And the linear self-similarity of the velocity deficit caused by the platform also suggests that a linear model is feasible. Moreover, recently-discovered existence and analytical solution of the Reynolds stress self-similarity in the turbine wake were confirmed experimentally in this study. As the wake develops, the center of the Reynolds stress increment profiles drifts upward while the center of mean velocity deficit profiles remains at the same height. Furthermore, energy transport analysis confirmed the interaction effects between the rotor wake and platform wake. The results of this study will be useful for the design of the whole wind farm with more accuracy, which considers the influence of the platform on the flow field between neighbor wind turbines. Highlights: A novel analytical wind turbine wake model including support structure is developed. Interaction between the platform and rotor wakes is revealed with energy transport analysis. Self-similarity in Reynolds stress of turbine wake is experimentally confirmed.